(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
In the article, the need for physical education and physical development of children through the use of physical exercises and national and active games for preschool children is scientifically and theoretically based. The direct and indirect impact on children’s physical development through physical exercises, national and active games is scientifically based, and at the same time, it is possible to develop competence in the field of children’s physical development and the formation of a healthy lifestyle.